2014
DOI: 10.1111/eje.12115
|View full text |Cite
|
Sign up to set email alerts
|

Faculty development for clinical teachers in dental education

Abstract: The faculty development program presented confirms that faculty development activities for clinical teachers based on theories of learning and experiences documented in the literature can be implemented with positive outcomes for individual teachers and for the learning environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…4,5,9,20,[22][23][24] Our study joins the recently published one conducted at the University of the Pacific in including the perceptions of dental school staff members in assessments, affirming that working in a humanistic environment is an important issue for them as well. The presentation included a recommendation for a coffee shop/cafeteria in the School of Dentistry to provide a space where the community could come together informally.…”
Section: Micro-aggressions and Bullyingmentioning
confidence: 67%
See 3 more Smart Citations
“…4,5,9,20,[22][23][24] Our study joins the recently published one conducted at the University of the Pacific in including the perceptions of dental school staff members in assessments, affirming that working in a humanistic environment is an important issue for them as well. The presentation included a recommendation for a coffee shop/cafeteria in the School of Dentistry to provide a space where the community could come together informally.…”
Section: Micro-aggressions and Bullyingmentioning
confidence: 67%
“…The top five recommendations based on multiple sources of data from the study The need for faculty development has been stressed in many studies to improve faculty well-being and work-life as well as education innovation and student learning. 4,5,9,20,[22][23][24] Our study joins the recently published one conducted at the University of the Pacific in including the perceptions of dental school staff members in assessments, affirming that working in a humanistic environment is an important issue for them as well. 25 Fourth, all three groups in our study indicated that it was not always easy for them to feel comfortable with others at the school regardless of their position.…”
Section: Micro-aggressions and Bullyingmentioning
confidence: 67%
See 2 more Smart Citations
“…In other words, students in this study had succesfully articulated the need of good clinical supervision, which is characterized by friendly communication and provide the kind of questions that focused on the case (good quality of questions). 20 In addition to positive and negative sides, the impacts of the requirement system can be seen from its compliance with the principle of six conceptions of learning. These learning conceptions are proposed by Säljö as many as five conception and by Van Rossum and Taylor as many as one additional conception.…”
Section: 19mentioning
confidence: 99%